Direct visualization of percolation paths in carbon nanotube/polymer composites - Malhofer, Andreas; Rother, Marcel; Zakharko, Yuriy; Graf, Arko; Schießl, Stefan Patrick; Zaumseil, Jana (Organic electronics, 2017)
Composites of single-walled carbon nanotubes (SWNT) and conjugated polymers are highly interesting as active semiconducting layers in solution-processable and flexible electronics. Understanding the percolation behavior and percolation threshold for electrical conductivity in these composites is a prerequisite for future applications. Here, we investigate the concentration and length dependence of on-currents and apparent mobilities for selectively dispersed, semiconducting (6,5) single-walled carbon nanotubes in a matrix of the dispersing polyfluorene-bipyridine copolymer (PFO-BPy) through field-effect transistor measurements. More importantly, we directly visualize the percolation paths at and above the percolation limit by near-infrared electroluminescence (EL) imaging with high spatial resolution. EL imaging reveals the various shapes of critical percolation paths at the threshold and the non-uniformity of charge transport even at high SWNT concentrations. We also find that percolation paths differ depending on the assignment of the injecting electrodes probably due to different injection barriers and variation of nanotube density at the electrodes.